Current Diagnosis, Treatment and Clinical Challenges in the Management of Lipodystrophy Syndromes in Children and Young People - Samim Özen; Barış Akıncı; Elif A. Oral (Galenos Yayincilik, 2020)
Lipodystrophy is a heterogeneous group of disorders characterized by lack of body fat in characteristic patterns, which can be genetic or acquired. Lipodystrophy is associated with insulin resistance that can develop in childhood and adolescence, and usually leads to severe metabolic complications. Diabetes mellitus, hypertriglyceridemia, and hepatic steatosis ordinarily develop in these patients, and most girls suffer from menstrual abnormalities. Severe complications develop at a relatively young age, which include episodes of acute pancreatitis, renal failure, cirrhosis, and complex cardiovascular diseases, and all of these are associated with serious morbidity. Treatment of lipodystrophy consists of medical nutritional therapy, exercise, and the use of anti-hyperglycemic and lipid-lowering agents. New treatment modalities, such as metreleptin replacement, promise much in the treatment of metabolic abnormalities secondary to lipodystrophy. Current challenges in the management of lipodystrophy in children and adolescents include, but are not limited to: (1) establishing specialized centers with experience in providing care for lipodystrophy presenting in childhood and adolescence; (2) optimizing algorithms that can provide some guidance for the use of standard and novel therapies to ensure adequate metabolic control and to prevent complications; (3) educating patients and their parents about lipodystrophy management; (4) improving patient adherence to chronic therapies; (5) reducing barriers to access to novel treatments; and (5) improving the quality of life of these patients and their families.